Halal Perspective Review of Cultured Meat Stem Cell Method - Qudsiyah, Ussy Siti; Tsania, Amany Awfa (Journal of Agri-Food Science and Technology, 2024)
Cultured meat is meat made in vitro based on cells or biotechnology meat that can replace animal meat products in general. The halal status of cultured meat is still a matter of debate in society. The aim of writing this systematic literature review is to discuss the halal status of cultured meat. The method used in writing this systematic literature review is based on the results of a systematic literature review; several researchers used Google Scholar, ScienceDirect, and other applications such as Microsoft Excel. SLR is an effort to make the often subjective literature review more objective to reduce researcher bias. This paper uses a systematic literature review to review published studies on halal perspectives of cultured meat. The relevant material was accessed and sourced from Google Scholar databases with a publication period from 2022-2024 and provide open access journals. Research results show that animal cells taken from animals that have been slaughtered according to Islamic law and rules are said to be halal for consumption. However, if the production of cultured meat comes from non-halal animals or from halal animals but the slaughter is not in accordance with Islamic law and rules, then it is haram for consumption.